Faktor-Faktor Pendorong dan Penghalang Pensiun Dini Pegawai Negeri Sipil (PNS) di Sumatera Barat - Putra, Ideal (Jurnal Demokrasi, 2006)
The aims of this research are to identify some determinant factors that may motivate and inhibit Indonesian public servants to retire early from their jobs. This study was conducted in four regencies and cities in the area of West Sumatera province and in the province government itself. The qualitative method was used in this research. Based on data analysis, it is found that there are some internal factors that motivated public servant to retire early like work saturartion, depression in career or promotion, or desire to do a new career. There are also external factors that motivated them to retire early like health hinderances and the good chances or opportunities in new jobs. Besides, there are also some inhibitions for the public servants to retire early and still remain in their current jobs until their regular retiring period. Â  Kata kunci: Pegawai Negeri Sipil, pensiun, pensiun dini, faktor internal, faktor eksternal